2017
DOI: 10.1016/j.jcm.2017.08.003
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Evaluation of Scapular Positioning in Patients With Nonspecific Chronic Low Back Pain: A Case-Control Study

Abstract: Objective: The purpose of this study was to investigate the position of scapula in patients with nonspecific chronic low back pain. Methods: A total of 17 participants with a history of nonspecific chronic low back pain and 17 healthy participants in the same age, sex, and weight range were enrolled in this case-control study. Lateral scapular slide test and Lennie test were used for clinical evaluation of scapular position in the frontal plane using a tape measure. The data were analyzed using an independent … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 10 publications
1
0
0
Order By: Relevance
“…Our study, however, did not find a statistically significant difference between groups with a slight increase in the degree of scapular upward rotation measured at 0 and 45 degrees of abduction in subjects with CNSLBP. This is consistent with the work of Taghizadeh et al (33) who found increased scapular upward rotation at zero-and 40-45-degrees abduction in subjects with CNSLBP as compared to healthy controls. They used, however, the lateral scapular slide test for assessment, while in our study, we used an inclinometer-based assessment.…”
Section: Discussionsupporting
confidence: 93%
“…Our study, however, did not find a statistically significant difference between groups with a slight increase in the degree of scapular upward rotation measured at 0 and 45 degrees of abduction in subjects with CNSLBP. This is consistent with the work of Taghizadeh et al (33) who found increased scapular upward rotation at zero-and 40-45-degrees abduction in subjects with CNSLBP as compared to healthy controls. They used, however, the lateral scapular slide test for assessment, while in our study, we used an inclinometer-based assessment.…”
Section: Discussionsupporting
confidence: 93%